Exploring Personal Yidam Practices in Vajrayana Tradition: A Journey to Enlightenment - Phuntsho, Dorji (International Journal of Humanities and Education Development (IJHED), 2024)
Personal Yidam practices in the Vajrayana tradition serve as a meaningful pathway to uncover one's inherent Buddha nature and nurture enlightened qualities. These practices, deeply rooted in ancient teachings and lineage transmissions, provide a direct path for individuals to engage with the wisdom and compassion of meditational deities called Yidams. The study explores the essence of personal Yidam practices, exploring their purpose, methods, significance, and transformative potential. The primary aim of personal Yidam practices is to dissolve dualistic perceptions and awaken the practitioner's inherent potential for enlightenment. Through elaborate visualization techniques and concentrated meditation, practitioners immerse themselves in the divine qualities and enlightened attributes of their chosen Yidam deity. Guided by a spiritual teacher, practitioners select a Yidam that resonates with their temperament, aspirations, and spiritual path, embarking on a journey of inner transformation and realization. In conclusion, personal Yidam practices in the Vajrayana tradition represent a sacred journey of self-discovery, transformation, and enlightenment, rooted in devotion, wisdom, and compassion, these practices offer a direct path toward enlightenment, guiding practitioners to realize their fullest potential and embody the awakened mind of the Yidam.